Mortality Rates of Minor vs Major Lower Extremity Amputations in Diabetic Patients - Strašunskas, Karolis; Markevičiūtė, Vėtra (Acta medica Lituanica, 2025)
Background: Mortality rates between minor (e.g., removal of toes or part of the foot) and major (e.g., below- or above-the-knee) lower extremity amputations (LEA) vary significantly in diabetic patients. Other factors, including survival rates, rehabilitation outcomes, and healthcare burden, are also notably impacted by the type of amputation performed.Objective: This narrative review aims to analyze and compare mortality rates following minor and major LEA in diabetic patients, by highlighting key risk factors and their impact on patient outcomes.Methods: A narrative review of existing literature was conducted by using searches of PubMed and Google Scholar. Studies reporting mortality rates, risk factors, comorbidities, functional outcomes, and management strategies among diabetic patients undergoing minor and major LEA were included.Results: Major LEA is associated with significantly higher short- and long-term mortality rates, with five-year survival ranging from 10% to 48%, compared to 29% to 69% for minor LEA. The key risk factors for mortality include chronic renal disease, peripheral arterial disease, sepsis, and poor glycemic control. While minor LEA oﬀers better survival rates, it carries a higher risk of progression to major amputation if diabetes-related complications persist.Conclusion: The findings highlight the critical importance of early intervention, strict glycemic control, and multidisciplinary care to improve the survival and quality of life in diabetic patients undergoing LEA. Limb preservation strategies should be prioritised whenever possible, as minor amputations lead to better long-term outcomes. Future research should focus on refining risk stratification and optimizing rehabilitation programs to enhance patient prognosis post-amputation.
Keywords: diabetes mellitus; lower extremity amputations; mortality rates